Coral diversity indices along the Gulf of Aqaba and Ras Mohammed, Red Sea, Egypt - MOHAMMED SHOKRY AHMED AMMAR (Biodiversitas Journal of Biological Diversity, 2011)
Ammar MSA (2011) Coral diversity indices along the Gulf of Aqaba and Ras Mohammed, Red Sea, Egypt. Biodiversitas 12: 92-98. Eight sites extending from Ras Mohammed to the northern tip of the Gulf of Aqaba were surveyed for seven different indices of diversity. These sites are: Ras Ghozlani, Marsa Breika, Temple, Katy, Islands, Canyon, South Nuweiba and Marsa Muqabela. The study proved that the healthy condition can be expressed either by a high value of Shannon index or low value of these other indices. Canyon, having effective management, is considered as the healthiest site (based on Shannon species diversity H`) while South Nuweiba is the least healthiest of all sites because of the illegal destructive fishery overexploitation. Sites having old damage with improved values of richness indices and low values of dominance indices (healthy conditions) like Ras Ghozlani and Marsa Breika had enough time and effective management to improve their diversity, while sites with non improved diversity like Temple and Katy are characterized by sponge and ascidian domination representing potent competitors with corals beside the increased nutrients in those sites. Islands and Marsa Muqabela have low values of richness indices because Marsa Muqabela has the highest value of boring worms and considerable sediments.